2016
DOI: 10.1159/000447457
|View full text |Cite|
|
Sign up to set email alerts
|

Resilience Factors in Women with Severe Early-Life Maltreatment

Abstract: Introduction: Early-life maltreatment (ELM) has long-lasting negative consequences and is the most important general risk factor for mental disorders. Nevertheless, a number of maltreated children grow up to become healthy adults and have therefore been called ‘resilient'. The aim of the current study is to investigate ‘resilience factors' in the context of severe ELM. Method: The study was part of the large multicenter project Understanding and Breaking the Intergenerational Cycle of Abuse (UBICA). A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…Our study shows that resilient mothers do not show any disturbed mother-child interaction despite having faced severe ELM. Multiple factors contributing to resilience have been identified in studies from our work group [18] and from Afifi and Macmillan [19]. These include high emotion regulation capacities; secure attachments, including supportive relationships and a stable family environment; low perceived loneliness during childhood; low impulsivity; low levels of neuroticism; and high levels of extraversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that resilient mothers do not show any disturbed mother-child interaction despite having faced severe ELM. Multiple factors contributing to resilience have been identified in studies from our work group [18] and from Afifi and Macmillan [19]. These include high emotion regulation capacities; secure attachments, including supportive relationships and a stable family environment; low perceived loneliness during childhood; low impulsivity; low levels of neuroticism; and high levels of extraversion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors contributing to resilience have been identified. These include high emotion regulation capacities; secure attachments, such as supportive relationships and a stable family environment; low perceived loneliness during childhood; low impulsivity; low levels of neuroticism; and high levels of extraversion [18, 19]. As these factors include interpersonal support and security for the mother, one might think that these resilience-promoting factors could also support the mother in developing an appropriate and warm mother-child interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that irrespective of later psychopathology, mothers with ELM reported reduced social support and fewer friends during childhood than those without ELM. However, only those mothers with ELM who later developed a mental disorder (ELM and disorder) also had significantly elevated levels of neuroticism and reduced levels of extraversion (Hillmann, Neukel, Hagemann, Herpertz, & Bertsch, 2016). Hypercortisolism, as found in our study in children of mothers in the ELM and disorder group, has been shown to increase the child's risk to develop a mental disorder later in life (Gunnar & Vazquez, 2001; McCrory et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mütter, die frühe Gewalterfahrungen gemacht hatten, berichteten in einem standardisierten Interview von einer stärker wahrgenommenen Einsamkeit in der Kindheit und von weniger Freunden als die Vergleichsgruppe. Jene Mütter mit frühen Gewalterfahrungen, die zusätzlich im Verlauf ihres Lebens eine psychische Störung entwickelt hatten, zeigten auch auf der Ebene der Persönlichkeitseigenschaften eine höhere Ausprägung von Neurotizismus und eine geringere Ausprägung von Extraversion sowie ein vulnerableres Bindungsverhalten als Müt-ter ohne Gewalterfahrungen [18]. Auch im Bereich der sozialkognitiven Funktionen konnten Defizite festgestellt werden: Mütter mit im Vergleich zu Müttern ohne frühe Gewalterfahrungen hatten im Trend eine niedrigere Empathiefähigkeit [23].…”
Section: Einfluss Auf Die Mutter Die Mutter-kind-interaktion Und Die ...unclassified